Penerapan Pembelajaran Berbasis Proyek dalam Pembuatan Pupuk Organik Cair untuk Meningkatkan Literasi Lingkungan pada Siswa SMAN 1 Tembilahan - Chairul Mukiyat; Najwa Shefa Azzahra; Saniyatu Zahra; Sinta Norjannah Attamimi; Habib Al husein; Ridho Kurniawan; Kanaya Adila Pasha; Inka Willy Mardyana; Hana Angelina Simamora; Miftahul Jannah; Rabel Maulana; Ruhd Janed Karisma Hermawati; Elus Syahputra Efendi (Unri Conference Series: Community Engagement, 2025)
This community service activity aims to improve students' environmental literacy through project-based learning by utilizing household waste, particularly rice washing water, into Liquid Organic Fertilizer (LOF). The program was implemented at SMAN 1 Tembilahan by students from Universitas Riau as part of a thematic KKN initiative. The method used includes counseling and practical training through five main stages: initial assessment (pretest), concept delivery, group project implementation, result presentation, and post-assessment (posttest). The approach combined educational participation with contextual practice using the Project-Based Learning model. The pretest and posttest data show a significant increase in understanding, with the average class score rising from 77.75 to 98.96. The results indicate that LOF-based environmental education, delivered through interactive and contextual methods, effectively increases students’ awareness and competence in environmental literacy. This program also reinforces students' critical thinking, collaboration, and problem-solving skills by engaging them directly in real-world ecological solutions.